Optimization of Growth and Urease Production of Bacillus Tequilensis Through pH and Temperature Control - Abdullah Faisal Alshalif; Qais Ali Al-Maqtari; Norzila Othman; Mohammed A. Mansour (International Journal of Integrated Engineering, 2026)
This study investigates the influence of pH and temperature on the growth density and urease enzyme production of Bacillus tequilensis. Bacterial counts and enzyme activity were measured across a range of pH levels (5.75 to 14.24) and temperatures (24.3°C to 42.7°C). The results showed significant differences in bacterial growth and urease production based on these conditions. The highest bacterial growth (6.34 log10 CFU/mL) occurred at pH 10.00 and 42.7°C, while optimal urease activity was also observed under these conditions, indicating that slightly alkaline pH and high temperature are favorable for both bacterial proliferation and enzyme activity. Conversely, high alkalinity at moderate temperatures significantly inhibited bacterial growth, and acidic conditions combined with high temperatures resulted in minimal bacterial presence. The Response Surface Methodology (RSM) analysis highlighted temperature as the most significant factor affecting urease production, followed by pH. ANOVA confirmed the substantial impact of these variables, with the model explaining 81.83% of the variance. This study underscores the critical role of pH and temperature in optimizing bacterial growth and enzymatic activity, providing valuable insights for industrial and environmental applications.